2009
DOI: 10.2106/jbjs.h.00854
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Humeral Migration in Shoulders with Symptomatic and Asymptomatic Rotator Cuff Tears

Abstract: Proximal humeral migration correlates with rotator cuff tear size. Tears extending into the infraspinatus tendon are associated with greater humeral migration than is seen with isolated supraspinatus tears. Humeral migration resulting from symptomatic rotator cuff tears is greater than that resulting from asymptomatic tears. Additionally, there is a critical size for tendon tears resulting in humeral migration in painful shoulders. Although both pain and tear size influence glenohumeral kinematics in symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
135
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 190 publications
(152 citation statements)
references
References 22 publications
10
135
0
7
Order By: Relevance
“…Larger RC tear size (mean size 22.7 mm) was associated with pain in 1 low‐quality study 35. One study reported no association of RC tear size and symptoms, although in symptomatic tears >175 mm 2 , pain was correlated with tear size 30. Two high‐quality studies reported no association between RC tear size or location with pain, one of which was well‐adjusted 45, 48.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Larger RC tear size (mean size 22.7 mm) was associated with pain in 1 low‐quality study 35. One study reported no association of RC tear size and symptoms, although in symptomatic tears >175 mm 2 , pain was correlated with tear size 30. Two high‐quality studies reported no association between RC tear size or location with pain, one of which was well‐adjusted 45, 48.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 56 articles were included (41 cross‐sectional, 11 cohort, 4 case–control). Imaging modalities included 25 ultrasound 16, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 24 MRI 15, 16, 41, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 12 radiographs 27, 30, 49, 53, 55, 62, 65, 66, 67, 68, 69, 70, 3 bone scintigraphy 65, 71, 72, 2 PET 73, 74, and no computed tomography. Of these studies, 10 assessed associations with 2 imaging modalities (16, 27, 30, 41, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations